Concept of tourist and economic regionalization of Bosnia and Herzegovina with special reference to the Tuzla tourist-geographic region in the area of Northern Bosnia - Nezirović, Senada; Drešković, Nusret; Mirić, Ranko (Journal for Geography, 2018)
In this paper, the authors work on the basis of the present knowledge, especially in the interest of realization of the concept of long-term development of tourism, to point out the need and representational basis for the separation of tourist-geographic regions of Bosnia and Herzegovina. The basis of the functional tourist and economic regionalization of Bosnia and Herzegovina served the concept of separation of tourist-geographical regions. The research of tourism development of the Tuzla region within this work requires the spatial definition, ie the demarcation of the tourist region in the area of ​​Northern Bosnia. During the delimitation of the Tuzla tourist region, the former geo-tourist and economic concepts of the Northeast Bosnia-Herzegovina regionalization were taken into account with six proposals being made. For this purpose, a geographic analysis was carried out and proposals for certain corrections of the former physiognomic boundaries and the spatial coverage of regional units of the first and second level were made, along with the established guidelines for further research in this field. During the field research conducted, the emphasis was placed on the detailed attribution of tourism potential and their role in spatial organization and tourism development. Motives and goals basically come down to the need to establish a more effective coordination of tourism development at the Tuzla tourist region, linking tourism destinations, to a range of common development issues, and achieving greater efficiency of the overall economic development. This paper provides a short analysis of the areas where there are tourism resources and facilities with the dominant function of tourism, i.e. in which tourism can become a dominant economic activity.
Keywords: regionalization; Tuzla tourist region; tourism